Nanomaterials in Proteomics. (3rd April 2019) - Sun, Nianrong; Wu, Hao; Shen, Xizhong; Deng, Chunhui
Abstract: For a deep understanding of the human proteome, the first crucial step is always the effective separation of targeted proteins/peptides from complex samples. In mass spectrometry‐based proteomics, nanomaterials have emerged as a highly effective means to separate targeted proteins/peptides and increase their relative abundance, which is beneficial to conduct mass spectrometric analysis. In particular, nanomaterials with different specific functionalities have received great attention in ordinary proteomics, phosphoproteomics, and glycoproteomics, for which the easily recognizable characteristics of these proteomes take the primary responsibility, such as the hydrophobicity, phosphate groups, cis–diol structure, and hydrophilicity. This review mainly focuses on the recent design and preparation of nanomaterials with specific recognition ability, as well as their application in the aforementioned three types of proteomics. Abstract : Sample separation is an indispensable step in proteomics research . This review mainly focuses on the design, preparation, and separation application of nanomaterials in ordinary proteomics and posttranslational modification (PTM) proteomics from 2014 onward, and briefly surveys the separation performance of combinational nanomaterials in multi‐PTMs that mainly includes the separation of phosphopeptides and glycopeptides from one sample.